Engineered metal nanoparticles in the sub-nanomolar levels kill cancer cells - Vodyanoy V (Dove Medical Press, 2016)
Vitaly Vodyanoy,1 Yasmine Daniels,2 Oleg Pustovyy,1 William A MacCrehan,2 Shin Muramoto,2 Gheorghe Stan21Department of Anatomy, Physiology and Pharmacology, Auburn University College of Veterinary Medicine, Auburn, AL, 2Material Measurement Laboratory, National Institute of Standards and Technology, Gaithersburg, MA, USA Background: Small metal nanoparticles obtained from animal blood were observed to be toxic to cultured cancer cells, whereas noncancerous cells were much less affected. In this work, engineered zinc and copper metal nanoparticles were produced from bulk metal rods by an underwater high-voltage discharge method. The metal nanoparticles were characterized by atomic force microscopy and X-ray photoelectron spectroscopy. The metal nanoparticles, with estimated diameters of 1 nm–2 nm, were determined to be more than 85% nonoxidized. A cell viability assay and high-resolution light microscopy showed that exposure of RG2, cultured rat brain glioma cancer cells, to the zinc and copper nanoparticles resulted in cell morphological changes, including decreased cell adherence, shrinking/rounding, nuclear condensation, and budding from cell bodies. The metal-induced cell injuries were similar to the effects of staurosporine, an active apoptotic reagent. The viability experiments conducted for zinc and copper yielded values of dissociation constants of 0.22±0.08 nmol/L (standard error [SE]) and 0.12±0.02 nmol/L (SE), respectively. The noncancerous astrocytes were not affected at the same conditions. Because metal nanoparticles were lethal to the cancer cells at sub-nanomolar concentrations, they are potentially important as nanomedicine.Purpose: Lethal concentrations of synthetic metal nanoparticles reported in the literature are a few orders of magnitude higher than the natural, blood-isolated metal nanoparticles; therefore, in this work, engineered metal nanoparticles were examined to mimic the properties of endogenous metal nanoparticles.Materials and methods: RG2, rat brain glioma cells CTX TNA2 brain rat astrocytes, obtained from the American Type Culture Collection, high-voltage discharge, atomic force microscope, X-ray photoelectron spectroscopy, high-resolution light microscopy, zeta potential measurements, and 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay were used in this work.Results: Engineered zinc and copper metal nanoparticles of size 1 nm–2 nm were lethal to cultured RG2 glioma cancer cells. Cell death was confirmed by MTT assay, showing that the relative viability of RG2 glioma cells is reduced in a dose-dependent manner at sub-nanomolar concentrations of the nanoparticles. The noncancerous astrocytes were not affected at the same conditions.Conclusion: The engineered and characterized zinc and copper nanoparticles are potentially significant as biomedicine.Keywords: nanoparticles, XPS, atomic force, glioma cancer cell, zinc, copper